Respostas fisiológicas à aplicação de reguladores vegetais e nutrientes em videira ‘crimson seedless' - Amaro, Amanda Cristina Esteves [UNESP] (2014)
The present study aimed to evaluate the effect of foliar application of auxin (Ax), cytokinin (CK) and gibberellin (GA) mixture, isolated or combined with the cobalt (Co) and molybdenum (Mo) mixture, in 'Crimson Seedless' grapevine, analyzing their effects on photosynthetic activity duration, metabolism and development of the plant, as well as increase production and fruit quality. The experiments were conducted in Juazeiro - BA, Brazil, in a randomized block design with four treatments, six blocks, with four plants each. Treatments were: T1 - Control; T2 - CK+Ax+GA 1.8L ha-1, T3 - CK+Ax+GA 1.8L ha-1 + Co+Mo 1.0L ha-1, and T4 - CK+Ax+GA 1.8L h-1 + Co+Mo 1.5L h-1. The treatments applications were carried out in three phases: inflorescence primordial stage, when berries were with 6 to 8 mm in diameter and berries elongation. In the first experiment, the photosynthetic activity duration was assessed by evaluating gas exchanges in leaves that were marked soon after sprouting, until the end of the cycle. In the second experiment, were evaluated gas exchanges, antioxidant enzymes activities, levels of carbohydrates and chlorophyll at 3, 5, 7, 14 and 21 days after the 1st application, at 1, 3 and 5 days after 2nd application and at 1, 3 , 5, 7 , 14, 21 and 28 days after the 3rd application (DAA). Thus, plants maintained their photosynthetic activity during the whole cycle, until the end of evaluations, for 133 days after sprouting leaves. However, it was observed that the application of plant growth regulators and nutrients anticipating the moment when the leaves reached the maximum absorption rate of CO2, indicating that these treatments have optimized the photosynthetic process. At the same time, rates of CO2 assimilation and carboxylation efficiency began to show greater efficiency after 14 DAA, as well as higher levels of chlorophylls, carotenoids and sugar concentrations, as in the 1st far as ...